THE ISSUE OF THE COURT’S COMPETENCE TO RELEASE FROM CRIMINAL LIABILITY ON THE BASIS OF ACTIVE REPENTANCE - Hovhannisyan, Armen (State and Law, 2025)
In this article, the author, taking into account the various approaches developed in legal practice, raises the issue of whether the court can be regarded as an authorized body entitled to exempt a person from criminal liability on the basis of active repentance. On this matter, the author conducts a corresponding analysis and presents their own approaches. As a result, the author, also relying on the idea that discretionary criminal prosecution refers to the prosecutor’s ability, based on legal criteria and reasoned expediency, not to initiate or to terminate already initiated criminal proceedings, concludes that the existing practical approaches—according to which the court, by virtue of its function of administering justice, is already vested with the right to apply the institution of active repentance—are legally questionable. This includes concerns regarding the proper enforcement of the constitutional chain of “function – body – authority”․